The Effectiveness of the Problem-Based Flipped Classroom Learning Model to Improve Conceptual Understanding of Physics Teacher Candidates on Crystal Structure Material - Heni Rusnayati; Wawan Ruswandi; Tiara Husnul Khotimah (Universitas Pendidikan Indonesia, 2023)
The limited time allocation for lectures in the classroom is an obstacle to presenting student-centered learning. This is one of the factors that prospective physics teacher students experience conceptual difficulties, especially in crystal structure material. So the purpose of this study was to determine the effectiveness of the problem flipped classroom learning model on understanding the concepts of prospective physics teacher students on crystal structure material. This study used a quasi-experimental method with a one-group pretest-posttest research design. The subjects of this study were 16 students who took solid-state physics courses. Data analysis techniques were carried out using normality tests, homogeneity tests, and pretest and posttest average difference tests. Then test the N-gain to see the increase in the pretest and posttest results and continue with the effect size test using the effect size. The instrument used was a test of mastery of the concept of crystal structure material. The results of the paired sample t-test analysis show that the Problem Based Flipped Classroom significantly influences learning outcomes with a t value of 11.439 with a significance of 0.000. Students' understanding of crystal structure material has increased with an N-Gain of 0.75, which is in the high category. This means that the pretest and posttest scores have a high increase. While the results of the effect size test obtained a score of d = 2.86, which means that learning with the Problem Based Flipped Classroom has a strong effect on student learning outcomes on crystal structure material.